THE ROLE OF MUHAMMADIYAH IN BUILDING COMMUNICATION IN BUILDING THE RELATIONSHIP AMONG PEOPLE RELIGION IN LAMPUNG - Muhammad Machsun (DEMOKRASI, 2021)
The Qur'an as a revelation and text has messages that are intended for humans. Where the messages contain values as a way of life for humans. One of the values contained in the Qur'an is communication. communication as a process of interaction of someone with another person, group or organization where someone, group or organization declares something.This paper intends to explain what are the roles of Muhamadiyah in building communication in order to strengthen inter-religious relations. The result was in the Muhammadiyah communication referring to Qawlan Sadidan, Qawlan Baligha, Qawlan Karima, Qawlan Ma'rufan, Qawlan Layyina, Qawlan Maisura, in each activity such as socializing with the minister, giving advice to the governor. As a form of coordination with the government. Next is Facilitating and mediating FKUB of regency/city that is facing problems, harmony studies in several provinces, Making harmony village pilot projects, participating in recitation activities, and regular annual prayer.